AND ESSENTIALLY THAT’S ALL. APHASIA IN THE WORK OF DANIIL CHARMS - Manzone, Martina (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2018)
This study focuses on the analysis of incommunicability in Daniil Charms’s poetics from the thematic point of view, as well as the philosophical and formal one. Thanks to his precision, the scientific language has been chosen to describe these narrative phenomena, avoiding the creation of equivocal neologisms. As a matter of fact, scholars can find a direct and precise connection between Charms’s stylistic choices and the scientific definition of aphasia elaborated by Aleksandr R. Lurija, years before the official codification of the neuropsychological disease. Aphasia has been investigated in a selected range of texts, that includes prose, poetry and drama, analysing the narrative technics and the characters portrait used by the author to fight the silence or to solve a creative block. However, the role of aphasia in Charms’s works doesn’t only show a compositional effect, but it also expresses a form of denounce of the author’s artistic consciousness. Furthermore, an important part of this study is focused on the function of words in human and object existence. In the end, what remains is the writer’s tenacious attachment to life through his voice.